Development and Validation of the Computer-Administered Animated Activity Questionnaire to Measure Physical Functioning of Patients With Hip or Knee Osteoarthritis. Issue 2 (1st February 2014) - Terwee, Caroline B.; Coopmans, Charlotte; Peter, Wilfred F.; Roorda, Leo D.; Poolman, Rudolf W.; Scholtes, Vanessa A.B.; Harlaar, Jaap; de Vet, Henrica C.W.
Abstract : Background: Physical functioning of patients with hip or knee osteoarthritis is measured by self-report questionnaires and performance-based tests. However, performance-based tests often are not feasible. Objective: The aim of this study was to develop a computer-administered questionnaire (ie, the Animated Activity Questionnaire [AAQ]) to measure physical functioning in patients with hip or knee OA. By showing animations of activities, the influence of the patient's own reference frame is minimized. The AAQ measures the same aspects of physical functioning as performance-based tests do. Design: This was a development and preliminary validation (cross-sectional) study. Methods: A pilot version of the AAQ was developed using motion capture to analyze the movement of a person performing 7 daily activities. Different animations of the same activity were made with 2 to 5 levels of difficulty. For each activity, participants were asked to choose one animation that best corresponds to their own way of performing the activity. A preliminary validation study was performed to compare the AAQ with validated self-report questionnaires (Knee Injury and Osteoarthritis Outcome Score, Hip Disability and Osteoarthritis Outcome Score, and questionnaires on walking, stair climbing, and rising and sitting down) and performance-based tests (walking, Timed "Up & Go" Test, Timed Stair Test) in 33 patients with hip or knee osteoarthritis. Results: As expected, the AAQ showed a correlation above .70 (.79, 95% confidence interval=.61–.89) with the total score of the performance-based tests. On the subscore level, the results were partly as expected. Fifty-eight percent of the participants preferred the AAQ over self-report questionnaires and performance-based tests. Limitations: The findings need to be replicated in larger samples of patients because the sample size of the study was rather small. Conclusion: The AAQ might be a good alternative for measuring physical functioning of patients with hip or knee osteoarthritis. The AAQ can easily be adapted for use in other patient populations. However, further development and validation are needed.